2020
DOI: 10.3390/cancers12113295
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cirrhosis in Chronic Hepatitis B Patients Is Associated with Genetic Variations in DNA Repair Pathway Genes

Abstract: Liver cirrhosis (LC), contributing to more than 1 million of deaths annually, is a major healthcare concern worldwide. Hepatitis B virus (HBV) is a major LC etiological factor, and 15% of patients with chronic HBV infection (CHB) develop LC within 5 years. Recently, novel host genetic determinants were shown to influence HBV lifecycle and CHB course. DNA repair enzymes can affect dynamics of liver damage and are involved in HBV covalently closed circular DNA (cccDNA) formation, an essential step for viral repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The study of genetic variations in repair genes has aided the understanding of various pathological mechanisms, describing risks associated with both individual and population genotypes based on the exposure of cells to xenobiotics that lead to genomic instability [ 10 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of genetic variations in repair genes has aided the understanding of various pathological mechanisms, describing risks associated with both individual and population genotypes based on the exposure of cells to xenobiotics that lead to genomic instability [ 10 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, various established etiologies of liver cirrhosis involve inflammation and oxidative stress as hallmarks of pathogenesis. 26,27 In this regard, variations in genes involved in the antioxidant enzymes, 28 DNA repair pathway, 29 immunologically important signaling pathways, and other players in combating oxidative damage were identified as predisposing factors of the disease. 30 Hence, patients with a family history of liver disease would have a lower likelihood of developing cryptogenic hepatic cirrhosis, which is no surprise.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that inflammation and oxidative stress play a pathogenic role in liver injury that progresses to liver cirrhosis due to exposure to viral and environmental factors. 45 , 46 This could be explained by genetic alterations in different cellular signaling pathways linked with DNA repair, 47 and immune response. 48 Furthermore, liver metabolic enzymes, both Phase I and Phase II, have a range of genetic polymorphisms that cause genetic predisposition in activation and/or detoxification functions, influence metabolism, and subsequently increase the toxicity of environmental chemical toxins like AFB 1 .…”
Section: Discussionmentioning
confidence: 99%